Analysis of students mistakes in solving open ended question based on Newman’s procedures on Treffinger learning model - Haryanto, Clarasati; Pujiastuti, Emi (Unnes Journal of Mathematics Education, 2020)
The purpose of this study was to determine the types of errors and causes of student errors in terms of the Newman procedure in solving open-ended questions on geometry and to determine the quality of learning using the contextual-based Treffinger model and achieving classical completeness. This research is a mix methods research. The design used in quantitative research is the Pre-Experimental Design with the type of One-Shot Case Study Design.The population in this study was 8th grade of SMP Muhammadiyah 8 Semarang with a sample of 8th U1 grade. Six students were selected as research subject. The data were taken by observation, interview, test and analyzed by using classical and descriptive qualitative learning mastery test. The results showed that an error in understanding the problem was carried out by one subject in the medium group and all subjects in the lower group, a transformation error was carried out by one subject in each group, an error in processing ability was carried out by all subjects in the upper group and one subject in the medium or medium group, then writing errors were made by all subjects in the upper group and one subject in the medium group. The cause of misunderstanding the problem is that students do not understand the problems listed on the questions. The cause of the transformation error is that students do not know the strategy used. The cause of processing ability errors is that students cannot determine the calculation correctly. Writing errors were caused by students not being careful in writing answers. The quality of learning in the contextual-based Treffinger model and the students' ability to solve open-ended questions on geometry using the contextual-based Treffinger model achieve classical learning completeness.